2011
DOI: 10.1007/s10973-011-1771-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the use of FTIR spectroscopy with DSC in the characterisation of melting and crystallisation in polycaprolactone

Abstract: The infra-red spectrum of polycaprolactone has been recorded as a function of temperature in the range where melting and crystallisation of the polymer can occur. Examination of the carbonyl band of the spectra reveals a clear morphological sensitivity; heating the semi-crystalline polymer through the melting region results in a decrease in the intensity of the crystalline component of the carbonyl band. Accordingly, there was a subsequent increase in intensity of the crystalline carbonyl band on cooling. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 11 publications
(10 reference statements)
3
33
0
2
Order By: Relevance
“…En la figura 3 (a), se observa las transiciones térmicas de los polímeros, la TC y las membranas de PCL/CS con carga de TC. La policaprolactona (PCL) muestra un solo pico endotérmico correspondiente al punto de fusión (T m ) a 62.08 • C con una entalpía de 67.85 J/g, muy cercanos a los valores reportados por Murphy et al [36], el análisis de quitosano (CS) mostró un primer pico endotérmico muy amplio en 82.48 • C debido a la eliminación de agua libre (desacetilación), tiene una entalpía de 273.3 J/g, García et al [37] reportan esta eliminación de agua (ver figura 3 (c)); además, se detectó un pico exotérmico en 283.74 • C que podría ser debido a la descomposición de las cadenas de quitosano con una entalpía de 60.04 J/g. La causa de la diferencia en la T m de estos polí-meros puede ser debido a que las propiedades térmi-cas de quitosano dependen del grado de acetilación, cristalinidad y peso molecular medio [38,39].…”
Section: Transiciones De Fase Por Temperatura Deunclassified
See 1 more Smart Citation
“…En la figura 3 (a), se observa las transiciones térmicas de los polímeros, la TC y las membranas de PCL/CS con carga de TC. La policaprolactona (PCL) muestra un solo pico endotérmico correspondiente al punto de fusión (T m ) a 62.08 • C con una entalpía de 67.85 J/g, muy cercanos a los valores reportados por Murphy et al [36], el análisis de quitosano (CS) mostró un primer pico endotérmico muy amplio en 82.48 • C debido a la eliminación de agua libre (desacetilación), tiene una entalpía de 273.3 J/g, García et al [37] reportan esta eliminación de agua (ver figura 3 (c)); además, se detectó un pico exotérmico en 283.74 • C que podría ser debido a la descomposición de las cadenas de quitosano con una entalpía de 60.04 J/g. La causa de la diferencia en la T m de estos polí-meros puede ser debido a que las propiedades térmi-cas de quitosano dependen del grado de acetilación, cristalinidad y peso molecular medio [38,39].…”
Section: Transiciones De Fase Por Temperatura Deunclassified
“…La pérdida de peso de la membrana de PCL/CS con carga de TC se aprecia a una temperatura de 345.7 • C con una pérdida de masa que se relacionó con un descenso del 90.39 %, esto en comparación con la PCL por presentar mayor porcentaje de polímero en la disolución y que la policaprolactona mostró un punto a 385.12 • C que corresponde al cambio relevante en la rapidez de pérdida de masa y que se relacionó con un descenso del 97.82 % en 40.21 • C, visto como una caída casi vertical en el termograma TGA desde una temperatura de 385.12 • C a 425.33 • C [36]. La pérdida de peso del quitosano (CS) se aprecia con un 56.86 % a una temperatura de 264.8 • C debido a la presencia de un grupo amino libre en su estructura.…”
Section: Transiciones De Fase Por Temperatura Deunclassified
“…Moreover, ozone treatment causes considerable decrease of intensity of band at 1,720 cm -1 ascribed to ester C=O stretching. This indicates that the treatment results in the reduction of ester linkages in polymer chains [15]. The absence of extra bands that can be assigned to carbonyl moiety in spectra of ozonized polymers implies that in this case ozonization does not lead to carbonyl formation.…”
Section: Ftirmentioning
confidence: 92%
“…of BL3 before and after ozone treatment. The feature is representative for all studied polymers In spite of the above mentioned in the case of BL1 and BL2 copolymers, the disrupted chains were not able to improve the mobility of segments which therefore prevented the regrouping of regularity, as inferred from the reduction in phase transition enthalpy [15,19]. In the case of BL2 copolymer, where the load of aliphatic fragments was at 30 wt% the melt enthalpy reduction was drastic, i.e.…”
Section: Thermal Propertiesmentioning
confidence: 94%
“…A screening of the literature data has shown that among others, thermoanalytical and spectroscopic techniques can be used to a large extent in the drug and food analysis. Numerous papers published recently revealed some examples of usefulness of differential scanning calorimetry (DSC) [7][8][9][10][11], thermogravimetry (TG) [7,8,12,13], Fourier-transform infrared (FTIR) [10,[13][14][15], near infrared (NIR) [11,14,16] and Raman [9,14,[17][18][19][20] techniques for analytical purposes.…”
Section: Introductionmentioning
confidence: 99%